Model-Switched Beamformer with Large Dynamic Range - Zeng Hao; Xing Qian; Yang Qingkun; Feng Linfeng (International Journal of Antennas and Propagation)
The strong desired signal will be mitigated due to “self-nulling” for the adaptive beamformer, even if the array calibration is used. The proposed methodology switches the models between phased array and adaptive array. In general, the system utilizes Frost adaptive beamforming. However, it will be switched to phased array if the “self-nulling” appears. According to the estimation of the array pattern at the direction of desired signal, we can determine if the “self-nulling” happens. The new approach is much easier to implement compared with the various robust beamforming algorithms.